The recolonization of lynx from central to southern Sweden : A success story - Hemmingmoore, Heather (2023)
The recolonization of large carnivores into their historic range is characterized by ecological and anthropogenic challenges. This thesis explores the natural range expansion of the Eurasian lynx (Lynx lynx) into southern Sweden, the last region to be recolonized following near extirpation from Sweden in the 20th century. I first define three criteria for a recolonization to be successful: there must be 1) availability of quality habitat, 2) sufficient mate availability to facilitate growth, and 3) sufficient genetic diversity to prevent inbreeding. Underpinning these requirements is the need for connectivity to ensure animals can reach suitable habitat and remain connected to the source population. To answer the question as to whether this recolonization event was successful, I first used resource selection functions to identify suitable habitat (Paper I), then used Bayesian population growth models to assess whether inverse density dependence affected population growth during population establishment (Paper II). I then used population genomics to check for genetic structure resulting from recolonization (Paper III), and examined the network of individual relatedness to better understand connectivity during recolonization (Paper IV). The resource selection study predicted extensive suitable habitat in southern Sweden, which was validated with establishment data during recolonization. It also revealed that dispersing individuals were less selective than established lynx (Paper I). Our Bayesian population growth models found that the population in southern Sweden grew more slowly than that of centralSweden during prior recolonization, although an Allee effect was unlikely, indicating sufficient connectivity even at low population densities (Paper II). The genomic analysis showed no spatial or temporal population structure, again indicating connectivity (Paper III). Individual relatedness patterns found no isolation by distance or resistance (Paper IV). The lynx population was able to establish in southern Sweden ...